2005
DOI: 10.1007/s00418-005-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Independent differentiation of mammotropes and somatotropes in the chicken embryonic pituitary gland

Abstract: It has been reported that mammotropes in a rodent pituitary gland are derived from somatotropes via somatomammotropes (SMTs), cells that produce both growth hormone (GH) and prolactin (Prl). However, no studies have been done on the transdifferentiation of somatotropes in the chicken pituitary gland. In this study, in order to determine the origin of mammotropes, we studied detail property of appearance of chicken somatotropes, mammotropes and pit-1 cells and then evaluated the existence of SMTs in the chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…In the chick, Gh and Prl mRNA are observed in distinct subdomains of the embryonic pituitary gland from the onset of their expression. Based on the distinct localization of GH and PRL in the caudal and cephalic lobes, respectively, our data clearly support previous studies that suggest that these two cell types are unlikely to originate from a common somatolactotrope progenitor capable of producing both hormones (Fu et al, 2004;Zheng et al, 2006). However, these data do not preclude the possibility that somatotropes and lactotropes arise from a common ''pre-hormone'' progenitor that becomes distributed throughout both lobes of the pituitary gland prior to hormone expression.…”
Section: Temporal Appearance and Spatial Organization Of Somatotropessupporting
confidence: 85%
“…In the chick, Gh and Prl mRNA are observed in distinct subdomains of the embryonic pituitary gland from the onset of their expression. Based on the distinct localization of GH and PRL in the caudal and cephalic lobes, respectively, our data clearly support previous studies that suggest that these two cell types are unlikely to originate from a common somatolactotrope progenitor capable of producing both hormones (Fu et al, 2004;Zheng et al, 2006). However, these data do not preclude the possibility that somatotropes and lactotropes arise from a common ''pre-hormone'' progenitor that becomes distributed throughout both lobes of the pituitary gland prior to hormone expression.…”
Section: Temporal Appearance and Spatial Organization Of Somatotropessupporting
confidence: 85%
“…It is well established that the chicken anterior pituitary gland can be divided into two lobes, caudal and cephalic lobes by their morphological structures. We have reported that embryonic somatotropes were diVerentiated in the caudal lobe at E12 and that the cells did not transdiVerentiate to mammotropes (Zheng et al 2006). In this study, we clearly showed that corticosteroid treatment signiWcantly increased the staining intensity and number of GH mRNA-expressing cells in not only the caudal lobe but also the cephalic lobe of the pituitary gland.…”
Section: Discussionmentioning
confidence: 61%
“…Studies on somatotropes in the embryonic chicken pituitary gland have shown that somatotropes commence diVerentiation between embryonic day (E) 14 and E16 in the caudal lobe (Thommes et al 1987;Porter et al 1995). We have reported that growth hormone (GH) mRNA-expressing cells Wrst appear in the ventral region of the caudal lobe at E12 and are located in the caudal lobe of the chicken pituitary gland until adulthood (Zheng et al 2006). We also found that mammosomatotropes, which are thought to be the intermediate cell type in transdiVerentiation of somatotropes to mammotropes in the rodent (Frawley et al 1985;Frawley and Boockfor 1991), did not appear in the embryonic chicken pituitary gland, suggesting that chicken somatotropes and mammotropes independently diVerentiate in the normal state.…”
Section: Introductionmentioning
confidence: 97%
“…Zheng et al (2006) have studied the transdiVerentiation of somatotropes in the chicken pituitary gland. For this, they studied the details of appearance of chicken somatotropes, mammotropes and pit-1 cells and then evaluated the existence of SMTs in the chicken embryonic pituitary gland.…”
Section: Hormone Cell Biologymentioning
confidence: 99%